Gender-inclusive business models in livestock value chains in low- and middle-income countries: What can we learn from the literature? - Baltenweck, Isabelle; Ouma, Emily A.; Nagujja, Janet (Frontiers Media, 2022)
Gender inequality is one of the key challenges of the twentyfirst century. Gender equality is one of the sustainable development goals (SDGs) and getting a more equal society is increasingly seen as supporting the achievement of the other SDGs. At the same time, the question remains: how to support gender equality in practice? This paper looks at gender-inclusive business models in the livestock sector. Such models can contribute to women's economic empowerment (an intermediate indicator toward gender equality) directly by addressing barriers to women's participation in livestock markets, or indirectly by involving them as implicit beneficiaries where such businesses provide services or products in circumstances where women face constraints such as poor access to inputs. A review of the literature was conducted to assess inclusive business models that are successful in increasing women's participation in livestock or livestock products marketing and its associated benefits and outcomes, focusing on low- and middle-income countries. The review included peer-reviewed publications, gray literature, and websites from non-government organizations that implement inclusive business models. A literature search was conducted using Google scholar and Research4Life databases for publications since 2010. Websites from development and international organizations implementing inclusive business models were also searched. Data from included records were extracted according to a pre-defined extraction form. A total of 29 studies were included. Results from the review show scarcity of literature and lack of research rigor in the few studies that document outcomes associated with inclusive business models. The few studies on gender-inclusive business models are mainly on collective action and contract farming to support women and men farmers to access markets, inputs, and services. Tangible benefits for women involved are reported, including women empowerment and change in gender norms to some extent.